Biomechanical effects of screws of different materials on vertebra-pediculoplasty: a finite element study - Wang, Yan-Ni; Ren, Ya-Nan; Han, Jun; Chen, Chao; Sun, Xun; Di, Ming-Yuan; Dou, Yi-Ming; Ma, Xin-Long; Wang, Zheng; Du, Cheng-Fei; Yang, Qiang (Frontiers in Bioengineering and Biotechnology, 2023)
Background: The effects of cannulated screws made of polyetheretherketone (PEEK) on the biomechanical properties of the vertebral body during vertebra-pediculoplasty remain unclear. This study aimed to investigate whether PEEK screws have the potential to replace titanium alloy screws.Methods: The surgical model of two different materials of screws was constructed using the finite element method. The biomechanical effects of the two models on the vertebral body under different working conditions were compared.Results: ① The peak von Mises stress of PEEK screws was significantly lower than that of titanium screws, with a reduction ranging from 52% to 80%. ② The von Mises stress values for the injured T12 spine were similar for both materials. Additionally, the segmental range of motion and intervertebral disc pressure showed no significant difference between the two materials.Conclusion: PEEK screws demonstrated advantages over titanium screws and may serve as a viable alternative for screw materials in vertebra-pediculoplasty.